Medición y Simulación de conmutación de la red 4G LTE a 5G mediante una femtocelda en la zona centro de Riobamba. - Remache Estrella, Nataly Cristina (2023)
Wireless communication is underway in Ecuador but remains in its initial stage. Despite this technology's expectations and potential, issues must be addressed before widespread adoption can be achieved. Implementing 5G requires a robust infrastructure, including base stations and antennas, which entails significant investments by telecommunications companies. That is why the objective is to measure and simulate the transition from the 4G LTE network to 5G using a femtocell in the central area of Riobamba. Initially, measurements will be taken in the current commercial 4G LTE network to understand the resources it offers. Subsequently, the transition from this 4G LTE network to a native 5G network will be simulated using a femtocell. Upon the project's conclusion, a proposal for improving the existing 4G LTE service network will be presented, evaluating the feasibility of transitioning to 5G technology using the available resources in the current network. The use of femtocells will be presented as an economical and straightforward solution to access the services offered by 5G, potentially revolutionizing various industries such as healthcare, manufacturing, transportation, and more. Users are expected to benefit from these innovations once the technology becomes more widely available.